A comprehensive review of iatrogenic withdrawal syndrome in critically ill children - Samah Al-Harbi (SpringerOpen, 2024)
Abstract Background Benzodiazepines and opioids are commonly administered to severely ill children in the pediatric intensive care unit (PICU) for analgesia and sedation. Long-term opioid medication often results in iatrogenic withdrawal syndrome (IWS) as well as tolerance when the dosage of benzodiazepines and opioids are gradually lowered or entirely stopped. Objectives This review aimed to review and summarize existing knowledge and information on IWS in pediatrics. Conclusion IWS in critically ill children is difficult to diagnose and manage. However, detecting and successfully managing IWS is critical to minimizing potentially negative effects during a patient's ICU stay and after discharge. Further research is required to ascertain the exact and reliable prevalence of IWS among pediatric patients, as well as the benefits and drawbacks of existing assessment tools and treatments.